In situ transmission electron microscopy observation of the deformation and fracture processes of an epoxy/silica nanocomposite. Issue 6 (6th January 2022) - Wang, Pangpang; Maeda, Ryusei; Aoki, Mika; Kubozono, Tatsuya; Yoshihara, Daisuke; Shundo, Atsuomi; Kobayashi, Takaya; Yamamoto, Satoru; Tanaka, Keiji; Yamada, Sunao
Abstract : Contour map of the true strain of an epoxy/silica nanocomposite film under a tensile condition. Abstract : Herein, we report the in situ transmission electron microscopy observation of the deformation and fracture processes of an epoxy resin thin film containing silica nanoparticles under tensile strain. Under tensile strain, the dispersed silica nanoparticles in the composite arrest the progress of the crack tip and prevent crack propagation. Concomitantly, the generation and growth of nanovoids at the epoxy matrix/nanoparticle interfaces were clearly observed, particularly in the region near the crack tip. These nanovoids contribute to the dissipation of fracture energy, thereby enhancing the fracture toughness. We also analyzed the local distributions of the true strain and strain rate in the nanocomposite film during tensile testing using the digital image correlation method. In the region around the crack tip, the strain rate increased by 3 to 10 times compared to the average of the entire test specimen. However, the presence of large filler particles in the growing crack suppressed the generation of strain, potentially contributing to hindering crack growth.